Using telehealth clinical case vignettes to enhance clinical confidence and competence in veterinary students - Lubbers, Brian V.; Fajt, Virginia R.; Teller, Lori M.; Apley, Michael D.; Stillisano, Jacqueline (Frontiers in Veterinary Science, 2023)
Veterinarians contribute substantially to the health of their patients and enhance the communities in which they live. Delivery of veterinary curricula continues to evolve to ensure that veterinary graduates are prepared to meet their professional obligations on Day One of their careers. In this study, veterinary practitioners were recruited to deliver telehealth case rounds to veterinary students at Kansas State University and Texas A&M University. Case discussions were hosted virtually once per month in the 2020–2021 and 2021–2022 academic years for a total of 16 sessions. Each presenting practitioner was instructed to develop a brief presentation for a case routinely seen in their practice, and to discuss important clinical decision points in diagnosis, treatment and management. Cases could also highlight important ethical or communication issues encountered in veterinary medicine. The overall goals of this project were to increase the quantity and diversity of clinical cases to which veterinary students were exposed during their professional training and to evaluate the feasibility and acceptability of telehealth technology as a teaching strategy. Student participants were surveyed to determine the effectiveness of telehealth sessions in increasing overall confidence and competence in case management, and veterinary presenters were surveyed to determine motivations for participating in the project and perceived value of the telehealth sessions. More than 95% of students indicated that participation in telehealth sessions increased their clinical confidence and competence. Presenting practitioners unanimously indicated that they would participate in similar instruction in the future. Recommendations are provided to improve the educational experience for future adopters of telehealth teaching sessions.